Study on pyrolysis of oil palm solid wastes and co-pyrolysis of palm shell with plastic and tyre waste / Faisal Abnisa - Faisal, Abnisa (2015)
Biomass is a renewable resource that can potentially be used to produce biofuels via the pyrolysis process. Oil palm solid wastes are a rich biomass resource in Malaysia, and it is therefore very important that they be utilized for more beneficial purposes, particularly in the context of the development of biofuels. In this study, the oil palm solid wastes from the plantation and mill activities were characterized and then pyrolyzed to produce oil and byproducts (char and gas). The effects of lignocellulosic as well as the contents from the proximate and ultimate analyses in producing the oil and byproducts during the pyrolysis process were studied. The palm shell was then selected as a model of lignocellulosic biomass for further use as feedstock in the co-pyrolysis process. In co-pyrolysis, there have been several investigations performed such as the study of synergistic effects of the use of palm shell with plastic and palm shell with scrap tyre, the optimization study on the co-pyrolysis parameters via response surface methodology, and the study on the effect of stepwise co-pyrolysis temperature in optimizing the recovery of fuels. The results showed that the use of co-pyrolysis technique can improve the characteristics of pyrolysis oil, e.g., increase the oil yield, reduce the oxygen content, reduce the water content, and increase the calorific value of oil. Moreover, this technique also benefits to the increase in the quality of byproducts. However, similar with the pyrolysis of palm shell alone, the oil yield from co-pyrolysis also contains the aqueous phase. The result of this study showed that the recovery of liquid fuel from the aqueous phase was successfully performed using a catalytic conversion.